Dissolved organic matter signatures vary between naturally acidic, circumneutral and groundwater-fed freshwaters in Australia. (15th June 2018) - Holland, Aleicia; Stauber, Jenny; Wood, Chris M.; Trenfield, Melanie; Jolley, Dianne F.
Abstract: Dissolved organic matter (DOM) plays important roles in both abiotic and biotic processes within aquatic ecosystems, and these in turn depend on the quality of the DOM. We collected and characterized chromophoric DOM (CDOM) from different Australian freshwater types (circumneutral, naturally acidic and groundwater-fed waterways), climatic regions and seasons. CDOM quality was characterized using absorbance and fluorescence spectroscopy. Excitation emission scans followed by parallel factor (PARAFAC) analysis showed that CDOM was characterized by three main components: protein-like, fulvic-like and humic-like components commonly associated with various waters globally in the Openfluor database. Principal component analysis showed that CDOM quality varied between naturally acidic, circumneutral and groundwater-fed waters, with unique CDOM quality signatures shown for each freshwater type. CDOM quality also differed significantly within some sites between seasons. Clear differences in dominant CDOM components were shown between freshwater types. Naturally acidic waters were dominated by highly aromatic (as indicated by the specific absorbance co-efficient (SAC340 ) and the specific UV absorbance (SUVA254 ) values which ranged between 31 and 50 cm 2 mg −1 and 3.9–5.7 mg C −1 m −1 respectively), humic-like CDOM of high molecular weight (as indicated by abs254/365 which ranged from 3.8 to 4.3). In contrast, circumneutral waters were dominated by fulvic-like CDOM of lower aromaticity (SAC340 : 7–21 cm 2 mg −1 and SUVA254 : 1.5–3.0 mg C −1 m −1 ) and lower molecular weight (abs254/365 5.1–9.3). The groundwater-fed site had a higher abundance of protein-like CDOM, which was the least aromatic (SAC340 : 2–5 cm 2 mg −1 and SUVA254 : 0.58–1.1 mg C −1 m −1 ). CDOM was generally less aromatic, of a lower molecular weight and more autochthonous in nature during the summer/autumn sampling compared to winter/spring. Significant relationships were shown between various CDOM quality parameters and pH. This is the first study to show that different freshwater types (circumneutral, naturally acidic and groundwater-fed) contain distinct CDOM quality signatures in Australia, a continent with unique flora and geology. Graphical abstract: Highlights: Naturally acidic waters dominated by aromatic, humic-like, high MW DOM. Circumneutral waters dominated by less aromatic, fulvic-like DOM of lower MW. Groundwater-fed site contained more proteinous DOM of lowest aromaticity and MW. DOM was more autochthonous-like during summer/autumn than during winter/spring.